2012
DOI: 10.1111/j.1745-4514.2011.00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activities of Black and Green Kombucha Teas

Abstract: Kombucha is widely consumed as black tea fermented for 7–14 days. The aim of the present study was to compare the antimicrobial activities of two kombucha beverages originating from green and black teas fermented for 21 days and to characterize the antimicrobial compounds (heat resistance and pH stability). Green and black tea infusions were fermented with a traditional kombucha culture. The resulting kombucha antibacterial/antifungal activities against some pathogenic microorganisms, including human pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 19 publications
3
38
0
19
Order By: Relevance
“…Kombucha samples were sterilized by filtering them through a sterile microfilter (0.22 µm pore size), and they were then transferred into the wells in the agar plates. The plates were further incubated at 37 • C for 18-24 h. The zones of bacterial growth inhibition were then determined [17,18].…”
Section: Antimicrobial Activity Of Kombucha Teamentioning
confidence: 99%
“…Kombucha samples were sterilized by filtering them through a sterile microfilter (0.22 µm pore size), and they were then transferred into the wells in the agar plates. The plates were further incubated at 37 • C for 18-24 h. The zones of bacterial growth inhibition were then determined [17,18].…”
Section: Antimicrobial Activity Of Kombucha Teamentioning
confidence: 99%
“…It has also been demonstrated that the broth may contain antibiotic substances which give the antimicrobial property [24,26]. Some studies have demonstrated that Kombucha tea shows not only antibacterial activity but also antifungal activity [27]. The antifungal activity is attributed to the production and In vitro studies on human peripheral lymphocytes [76] presence of acetic acid in this beverage.…”
Section: Health Benefits Associated With Consumption Of Kombuchamentioning
confidence: 99%
“…The antifungal activity is attributed to the production and In vitro studies on human peripheral lymphocytes [76] presence of acetic acid in this beverage. In recent times, the immergence of resistant strains of pathogens associated with human diseases has been widely seen, and the use of Kombucha tea as an antimicrobial product can be used to overcome this problem [27]. In this aspect, it has been demonstrated that the antimicrobial activity of Kombucha tea prepared form green tea shows a higher activity than Kombucha tea prepared traditionally from black tea [27].…”
Section: Health Benefits Associated With Consumption Of Kombuchamentioning
confidence: 99%
“…It is known that kombucha tea is a detoxyfi ng and energizing drink, exhibiting hypoglycemic, hypocholesterolemic, and antioxidative activity (Bhattacharya et al 2013;Shenoy, 2000;Yang et al 2009). Kombucha is a source of antimicrobials, and can prevent hepatotoxicity and cancer (Afsharmanesh and Sadaghi, 2014;Battikh et al, 2012;Jayabalan et al, 2011). Kombucha contains tea leaves brewing, which health eff ect and antioxidants composition is greatly acknowledged (Gramza-Michałowska, 2014;Gramza-Michałowska et al, 2007;Kujawska et al, 2016a;2016b;Mika et al, 2015).…”
Section: Research On the Effect Of Culture Time On The Kombucha Tea Bmentioning
confidence: 99%